The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7314/apjcp.2014.15.16.6679
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogues Do Not Prevent Carcinoid Crisis

Abstract: Background: Carcinoid crisis is a life-threating syndrome of neuroendocrine tumors (NETs) characterized by dramatic blood pressure fluctuation, arrhythmias, and bronchospasm. In the era of booming anti-tumor therapeutics, this has become more important since associated stresses can trigger carcinoid crisis. Somatostatin analogues (SSTA) have been recommended for prophylactic administration before intervention procedures for functioning NETs. However, the efficacy is still controversial. The aim of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…As previously reported for neuroendocrine tumors, heterogenous distribution of somatatostatin receptors between tumor cells and hence higher number of cells lacking somatostatin receptors may have influenced treatment results (Wynick D et al, 1989). However, in a meta analysis has shown that the efficacy of somatostatin analogue octreotide treatment for preventing carcinoid crisis remains controversial (Guo and Tang, 2014).…”
Section: Expectations Of Response From Octreotide Therapy In Recurrentmentioning
confidence: 99%
“…As previously reported for neuroendocrine tumors, heterogenous distribution of somatatostatin receptors between tumor cells and hence higher number of cells lacking somatostatin receptors may have influenced treatment results (Wynick D et al, 1989). However, in a meta analysis has shown that the efficacy of somatostatin analogue octreotide treatment for preventing carcinoid crisis remains controversial (Guo and Tang, 2014).…”
Section: Expectations Of Response From Octreotide Therapy In Recurrentmentioning
confidence: 99%
“…Based on these observations, (pre)treatment with octreotide is recommended for therapeutic interventions in functional midgut NET. Although some drugs have been successfully used in certain cases, for example, cyproheptadine, ketanserin, 5-HT receptor antagonists, corticosteroids, and H1- and H2-receptor antagonists [ 15 ], somatostatin analogues are considered most effective and are recommended as first-line therapy [ 8 , 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An excessive release of these active substances caused by different triggers like surgery/anaesthesia, interventional diagnostic and therapy, radionuclide therapy, medication, and examination can lead to carcinoid crisis characterized by dramatic blood pressure fluctuation, arrhythmias, bronchospasm, and mental disturbances [ 8 13 ]. Commonly, hypotension is the expected hemodynamic change; however a small group of carcinoid patients experiences hypertension during carcinoid crisis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peri-operative management: the surgical approach for CHD patients requires a highly skilled multidisciplinary team with broad experience, as anaesthesia can trigger carcinoid crisis and subsequent death in patients going for surgery. 26,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] The most crucial pre-operative anaesthetic management should encompass optimum control of carcinoid symptoms, and intensified and close monitoring of intra-operative blockade of serotonin receptors. Drugs that may stimulate the release of vasoactive substances from tumour cells should be avoided.…”
Section: Management Strategies For Chdmentioning
confidence: 99%
“…Drugs that may stimulate the release of vasoactive substances from tumour cells should be avoided. 26,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] The most important drugs to be avoided during the peri-operative period include histamine-releasing neuromuscular relaxants and opioids, as they are associated with detrimental outcomes in CHD patients. The introduction of somatostatin analogues remains a key component to prevent peri-operative carcinoid crisis, and the administration of larger doses of somatostatin analogue is highly recommended in CHD patients.…”
Section: Management Strategies For Chdmentioning
confidence: 99%